Exploring Deep Eutectic Solvents as Pharmaceutical Excipients: Enhancing the Solubility of Ibuprofen and Mefenamic Acid - Mihaela-Alexandra Nica; Valentina Anuța; Cristian Andi Nicolae; Lăcrămioara Popa; Mihaela Violeta Ghica; Florentina-Iuliana Cocoș; Cristina-Elena Dinu-Pîrvu (Pharmaceuticals, 2024)
Objectives: The study explores the potential of various deep eutectic solvents (DESs) to serve as drug delivery systems and pharmaceutical excipients. The research focuses on two primary objectives: evaluating the ability of the selected DES systems to enhance the solubility of two poorly water-soluble model drugs (IBU and MFA), and evaluating their physicochemical properties, including density, viscosity, flow behavior, surface tension, thermal stability, and water dilution effects, to determine their suitability for pharmaceutical applications. Methods: A range of DES systems containing pharmaceutically acceptable constituents was explored, encompassing organic acid-based, sugar- and sugar alcohol-based, and hydrophobic systems, as well as menthol (MNT)-based DES systems with common pharmaceutical excipients. MNT-based DESs exhibited the most significant solubility enhancements. Results: IBU solubility reached 379.69 mg/g in MNT: PEG 400 (1:1) and 356.3 mg/g in MNT:oleic acid (1:1), while MFA solubility peaked at 17.07 mg/g in MNT:Miglyol 812®N (1:1). In contrast, solubility in hydrophilic DES systems was significantly lower, with choline chloride: glycerol (1:2) and arginine: glycolic acid (1:8) showing the best results. While demonstrating lower solubility compared to the MNT-based systems, sugar-based DESs exhibited increased tunability via water and glycerol addition both in terms of solubility and physicochemical properties, such as viscosity and surface tension. Conclusions: Our study introduces novel DES systems, expanding the repertoire of pharmaceutically acceptable DES formulations and opening new avenues for the rational design of tailored solvent systems to overcome solubility challenges and enhance drug delivery.